Motivation in the workplace: a study on the support group employees of the International Islamic University Malaysia / Saiful Azwan Mustapha - Mustapha, Saiful Azwan (2014)
The purpose of this study is to explore the effect of work motivation on intention to stay of support group employees of Malaysian public university. In addition, job satisfaction is included as moderator to investigate the impact on the relationship between work motivations on intention to stay. The framework provides useful perspective for studying work motivation in Malaysia. The statistics show a number 'of IIUM support group staff leaving the workplace annually. Due to that, the remaining staff motivation was affected due to more responsibility to be covered.Personal relationship and personal growth was absent because of too much focus on work due to workload. Therefore, by this nature, employees expected the recognition from supervisors whereby supervisory style and benefits play a significant role in motivating support group staff in the workplace. This will at least maintain or even increase their motivation to fully serve the organization.Two hundred and twenty-two usable questionnaires were collected through the survey method. Respondents were the employees of the International Islamic University Malaysia (IIUM). SPSS version 16 was utilized to estimate the conceptual model. Descriptive analysis and hierarchical regression were utilized to derive the findings for the study. The findings show that work motivation has positive significant impact on intention to stay. Job satisfaction was proven to moderate the relationship between work motivations on intention to stay. However, out of seven elements of work motivation, collectively only recognition, and responsibility were positively significant to intention to stay.Job satisfaction moderates the relationship of work motivation to intention to stay when regressed collectively. This study provides an insight into the elements of work motivation of support staff of university in Malaysia. Identifying the weak elements of work motivation would give practitioners ways to solve their weaknesses in strengthening their human resources to retain good employees in the organization